INVENTARISASI PARASITOID PADA HAMA TANAMAN JAGUNG (Zea mays) DI KABUPATEN MINAHASA UTARA - Andreas P. Mambu; C.I. Salaki; N Wanta (Universitas Sam Ratulangi, 2016)
ABSTRACTNatural enemies known as biological organisms affecting the regulation of pest populations or other organism. In a habitat or ecosystem tropical agriculture are usually found in many types of biological agents that naturally regulate the balance of nature. Insect parasitoids is small or as large as the host in deadly parasites and their hosts. Parasitoid requires only one host to perpetuate the cycle of life. This research was conducted in the District Kauditan and Dimembe, North Minahasa Regency, North Sulawesi province in July to September 2012. The aim of the study is to determine the type of parasitoid pests of corn crops in the district and sub-district Kauditan Dimembe North Minahasa Regency. The results of this study are expected to be the basic data that are important in developing biological control, in order to increase production of corn in North Sulawesi. Retrieval of data using a survey method in two districts, and each district selected two villages, namely Kauditan and Dimembe. Parasitoids on corn crop in the region is no different with Kauditan Tatelu. Almost all kinds of parasitoids were found on corn plants were also found in maize nutmeg in Kauditan. Parasitoids were found on the ecosystem corn plants totaling 16 individuals.Keywords: Corn, Parasitoid